2002
DOI: 10.1084/jem.20020824
|View full text |Cite
|
Sign up to set email alerts
|

AML1-ETO Inhibits Maturation of Multiple Lymphohematopoietic Lineages and Induces Myeloblast Transformation in Synergy with ICSBP Deficiency

Abstract: The translocation (8;21), generating the AML1-ETO fusion protein, is one of the most frequent chromosomal abnormalities associated with acute myelogenous leukemia (AML). To elucidate its role in oncogenesis, bone marrow (BM) cells were infected with a retroviral vector carrying AML1-ETO and transplanted into mice. In contrast to previous transgenic mouse models, we show that AML1-ETO directly stimulates granulopoiesis, suppresses erythropoiesis, and impairs the maturation of myeloid, B, and T lymphoid cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
147
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 79 publications
14
147
2
Order By: Relevance
“…Subsequently, AML/ETO t(8;21) was transduced to bone marrow derived from mice deficient of the interferon regulatory factor ICSBP (Schwieger et al, 2002), implicated as a suppressor of myeloid neoplasia (Holtschke et al, 1996;Gabriele et al, 1999;Scheller et al, 1999) and was found to synergize with ICSBP deficiency to incite myeloblastic conditions evocative of AML. Furthermore, activating mutations in receptor tyrosine kinases, for example TEL/PDGFbR and Flt3, were found to cooperate with AML/ETO (Grisolano et al, 2003), NUP98/HOXA9 t(7;11) (Dash et al, 2002) and PML/RARa t(15;17) (Kelly et al, 2002) causing AML (FAB M2)-type leukaemia, AML and APL, respectively in transduced mice.…”
Section: Cdx2mentioning
confidence: 99%
“…Subsequently, AML/ETO t(8;21) was transduced to bone marrow derived from mice deficient of the interferon regulatory factor ICSBP (Schwieger et al, 2002), implicated as a suppressor of myeloid neoplasia (Holtschke et al, 1996;Gabriele et al, 1999;Scheller et al, 1999) and was found to synergize with ICSBP deficiency to incite myeloblastic conditions evocative of AML. Furthermore, activating mutations in receptor tyrosine kinases, for example TEL/PDGFbR and Flt3, were found to cooperate with AML/ETO (Grisolano et al, 2003), NUP98/HOXA9 t(7;11) (Dash et al, 2002) and PML/RARa t(15;17) (Kelly et al, 2002) causing AML (FAB M2)-type leukaemia, AML and APL, respectively in transduced mice.…”
Section: Cdx2mentioning
confidence: 99%
“…Analyses of various mouse models of AML1-ETO expression also demonstrate that AML1-ETO plays a critical role in leukemogenesis. By itself however, it is not sufficient for disease development [45][46][47][48][49]. Since AML1-ETO has the AML1 DNA binding domain and binds to the same DNA sequence as AML1, it has been believed that the function of AML1-ETO is through the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…147 In all three hematopoietic cell types, IRF8 expression decreased with aging. Previously, IRF8 insufficiency has been associated with the development of hematopoietic malignancies in murine models, 148,149 and many human hematopoietic malignancies (AML, CML, MDS) display decreased IRF8 expression. [150][151][152] These results suggest that IRF8 insufficiency with aging may facilitate transformation, but additional studies will be required to confirm these results and to identify potential other T-ARECs, if they exist.…”
Section: Effects Of Aging On Hematopoietic Expressionmentioning
confidence: 99%